THE INFLUENCE OF BRAND IMAGE AND DIGITAL MARKETING ON PURCHASE DECISIONS SKINTIFIC PRODUCTS - Dea Nadila; Naufal Bachri; Nursakinah Ritonga; Lisa Iryani; Maisyura (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of brand image and digital marketing on purchasing decisions for scientific products. This study uses descriptive quantitative research using non-probability sampling with purposive sampling technique. The population in this study were undergraduate students of the Faculty of Social and Political Sciences, Malikussaleh University who used or had used Skintific products. The sample obtained was 100 respondents. Data collected by survey method. The data analysis used in this study used multiple linear regression with the help of the SPSS 26.0 software program. Individual hypothesis testing shows that the brand image variable has a positive and significant effect on purchasing decisions with a sig. value of 0.015 <0.05 and a t count value of 5.258> t table 1.985. Then for the digital marketing variable, it has a positive and significant effect on purchasing decisions with a sig. value of 0.000 <0.05 and a t count value of 2.489> t table 1.985. While simultaneously showing that brand image and digital marketing both have a positive and significant effect on purchasing decisions with a sig. value of 0.000 <0.0 and a Fcount value of 26.029> Ftable 3.09.